2020
DOI: 10.1055/s-0040-1707231
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Chelated Ruthenium Olefin Metathesis Catalysts

Abstract: This Account summarizes the historical development of latent sulfur-chelated ruthenium precatalysts from the Lemcoff group’s perspective. The most unique feature of this family of complexes is that they appear in the more stable cis-dichloro configuration, which is latent towards olefin metathesis reactions. Activation of the precatalyst, brought about by isomerization from the cis-dihalo to the trans-dihalo forms, can be achieved either by thermal or light stimuli. Modifications of the ligand sphere bestows u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“… 38 It is observed that this approach focused on stereoselectivity differs from other sulfur chelates previously reported, in which the ether R 2 O→Ru in HG catalysts is replaced by a thioether R 2 S→Ru, resulting in enhancements in the catalytic activity. 39 44 It should be clarified, however, that we aimed at the formation of an active species that resembles the structure depicted in Scheme 2 b. In this regard, several authors have previously reported predictive catalysis based on DFT calculations verified by experimental evidence.…”
Section: Introductionmentioning
confidence: 99%
“… 38 It is observed that this approach focused on stereoselectivity differs from other sulfur chelates previously reported, in which the ether R 2 O→Ru in HG catalysts is replaced by a thioether R 2 S→Ru, resulting in enhancements in the catalytic activity. 39 44 It should be clarified, however, that we aimed at the formation of an active species that resembles the structure depicted in Scheme 2 b. In this regard, several authors have previously reported predictive catalysis based on DFT calculations verified by experimental evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this reaction has deeply impacted synthetic organic chemistry and materials and polymer science. , With the prospect of controlling metathesis and its mechanistic congeners with high levels of spatial and temporal control, interest in activating latent metathesis catalysts is steadily growing. , For instance, ring-opening metathesis polymerization (ROMP) is highly robust and creates mechanically strong polymers; however, its temporal control is still an ongoing challenge. Examples of controlling ROMP through different stimuli have emerged, including electro-, mechano-, and photochemistry. Of these, the use of light is highly attractive as it is a mild mode of activation while enabling precise spatial control with high resolution through lasers and excellent temporal control with the simple flip of the switch.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to photoactivate latent Ru complexes, such as by activating various benzylidene complexes via UV to visible light or generation of photoacids. Metal-free ROMP has been developed using a photocatalyst to oxidize enol ethers . We have previously described a bis- N -heterocyclic carbene (NHC)-coordinated Ru complex which when treated with blue light in the presence of an oxidizing photocatalyst leads to light-controlled olefin metathesis .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the ligand sphere of metal alkylidenes has been extensively studied, providing a wide range of olefin metathesis catalysts and reactions [2] . The introduction of ruthenium sulfur‐chelated benzylidenes [3] led to the development of precatalysts that display a latent cis ‐dihalo configuration. Because of their special disposition, these complexes require external energy, such as heat or irradiation, to isomerize to the active trans ‐dihalo isomer [4,5] .…”
Section: Introductionmentioning
confidence: 99%